MORPHOLOGICAL AND ANATOMICAL VARIATIONS OF FRUITS IN SOME TAXA OF VALERIANACEAE BATSCH FAMILY - & Saeed, Al-dabbagh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted at the different geographical regions at the north of Iraq; during the field trips, many samples of individuals of two genera Valeriana L. and Valerianella Miller were collected. The fruits of specimens morphologically have been inspected, and some parts of fruits were anatomically examined by paraffin method, from both studies the diagnostic characteristics of fruits were determined. This study was proved the morphological characteristics of significance within genera and species levels, while anatomical features had a large role in separation between the two studied genera, it was proved that the cross-sectional outlines of fruits played a significant role in delimiting among species of the genus Valerianella.